Effect of Office Layout on Employee Performance at Universitas Klabat - Paoki, Rouna (8ISC Abstract Proceedings, 2022)
Employee performance is a behavior that is shown by employee performance based on their role in the organization. This can be implemented well, which is supported by having a good office layout. The purpose of this study was to determine the description of office layout on employee performance at Universitas Klabat. The study was descriptive and quantitative data research. The results of this study showed that the office layout and employee performance are good, and the data analysis found there is a positive and significant effect between office layout and employee performance. The result of the correlation analysis shows that the value of r=0.736. The value of the coefficient determined (R square) of 0.542, which shows that employee performance is influenced by independent variable by 54.2%. Keywords : Employee Performance, Office Layout